Interatomic Coulombic decay cascades in multiply excited neon clusters - K. Nagaya (Nature Portfolio, 2016)
Interatomic Coulombic decay (ICD) is a relaxation of an atom in a weakly bound environment by the transfer of excess energy to ionize the neighbouring atom. Here the authors observe intra-Rydberg ICD in neon clusters, which is a decay that involves the ionization of Rydberg atoms in the cluster.